Faktor-faktor yang berhubungan dengan kepuasan pasien rawat jalan - Selfy Safitri; Adila Solida; Puspita Sari; Arnild Augina (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Backgroud: Patient satisfaction is an important indicator in assessing the quality of healthcare services. Good service quality can increase patient satisfaction, thereby encouraging optimal utilization of healthcare services. Purpose: To analyze factors associated with outpatient satisfaction. Method: This quantitative study used a cross-sectional design. The study was conducted at the Rawasari Community Health Center in Jambi City in 2026. A sample of 105 respondents was selected using incidental sampling. Data were collected through interviews using a questionnaire and analyzed using the Chi-Square test at a 95% confidence level (α = 0.05). Results: The majority of respondents, 69 respondents (65.7%), were satisfied with the services provided. Bivariate analysis showed a relationship between physical evidence and patient satisfaction (p=0.005), responsiveness (p=0.001), reliability (p=0.001), assurance (p=0.002), and empathy (p=0.001). Conclusion: All dimensions of SERVQUAL service quality have a significant relationship with outpatient satisfaction. Keywords: Community Health Center; Patient Satisfaction; SERVQUAL.